Efficient Degradation of 2,4,6-Trichlorophenol Requires a Set of Catabolic Genes Related to tcp Genes from Ralstonia eutropha JMP134(pJP4) - Matus, V. (American Society for Microbiology, 2003)
2,4,6-Trichlorophenol (2,4,6-TCP) is a hazardous pollutant. Several aerobic bacteria are known to degrade this compound. One of these, Ralstonia eutropha JMP134(pJP4), a well-known, versatile chloroaromatic compound degrader, is able to grow in 2,4,6-TCP by converting it to 2,6-dichlorohydroquinone, 6-chlorohydroxyquinol, 2-chloromaleylacetate, maleylacetate, and β-ketoadipate. Three enzyme activities encoded by tcp genes, 2,4,6-TCP monooxygenase (tcpA), 6-chlorohydroxyquinol 1,2-dioxygenase (tcpC), and maleylacetate reductase (tcpD), are involved in this catabolic pathway. Here we provide evidence that all these tcp genes are clustered in the R. eutropha JMP134(pJP4) chromosome, forming the putative catabolic operon tcpRXABCYD. We studied the presence of tcp-like gene sequences in several other 2,4,6-TCP-degrading bacterial strains and found two types of strains. One type includes strains belonging to the Ralstonia genus and possessing a set of tcp-like genes, which efficiently degrade 2,4,6-TCP and therefore grow in liquid cultures containing this chlorophenol as a sole carbon source. The other type includes strains belonging to the genera Pseudomonas, Sphingomonas, or Sphingopixis, which do not have tcp-like gene sequences and degrade this pollutant less efficiently and which therefore grow only as small colonies on plates with 2,4,6-TCP. Other than strain JMP134, none of the bacterial strains whose genomes have been sequenced possesses a full set of tcp-like gene sequences.